Effect of Basis Sets on the Selection of the Level of Theory Toward the Development of Quantum-Based Force Field Equation for Ionic Liquids - A. N. Soriano; B. T. Doma, Jr. (Department of Chemical Engineering, Universitas Gadjah Mada, 2005)
The chemical industry is under considerable pressure to replace many of the volatile organic compounds. Volatile organic compounds are a major contributor to air pollution, but out of necessity, they are still frequently used in many chemical and industrial processes. A new class of solvents, referred to as ionic liquids, may offer at least a partial solution to the pollution problem caused by volatile organic compounds. Ionic liquids are generally considered